People with low back pain want clear, consistent and personalised information on prognosis, treatment options and self-management strategies: a systematic review - Lim, Y.Z.; Chou, L.; Au, R.T.; Seneviwickrama, K.M.D.; Cicuttini, F.M.; Briggs, Andrew; Sullivan, K.; Urquhart, D.M.; Wluka, A.E. (AUSTRALIAN PHYSIOTHERAPY ASSOC, 2019)
Question: What health information needs are perceived by people with low back pain? Design: Systematic review of publications examining perceived health information needs related to low back pain identified through Medline, EMBASE, CINAHL and PsycINFO (1990 to 2018). Participants: Adults with low back pain of any duration. Data extraction and analysis: Two reviewers independently extracted descriptive data regarding study design and methodology, and assessed risk of bias. Aggregated findings of the perceived needs of people with low back pain regarding health information were meta-synthesised. Results: Forty-one studies (34 qualitative, four quantitative and three mixed-methods) were identified. Two major areas of perceived health information needs for low back pain emerged. The first major area was needs related to information content: general information related to low back pain, its cause and underlying pathology; strong desire for diagnosis and imaging; prognosis, future disability and effect on work capacity; precipitants and management of flares; general management approaches; self-management strategies; prevention; and support services. The second major area of needs related to how the information was delivered. People with low back pain wanted clear, consistent information delivered in suitable tone and understandable language. Conclusion: Available data suggest that the information needs of people with low back pain are centred around their desire for a diagnosis, potentially contributing to expectations for and overuse of imaging. People with low back pain expressed a strong desire for clear, consistent and personalised information on prognosis, treatment options and self-management strategies, related to healthcare and occupational issues. To correct unhelpful beliefs and optimise delivery of evidence-based therapy, patient and healthcare professional education (potentially by an integrated public health approach) may be warranted.